Evaluating the phylogenetic position of the monotypic family Halophytaceae (Portulacinae, Caryophyllales) based on plastid and nuclear molecular data sets - Anton, Ana Maria Ramona (2014)
In spite of numerous phylogenetic studies to determine relationships in Order Caryophyllales and particularly in the suborder Portulacinae, the position of Halophytaceae remains controversial. Halophytum ameghinoi belongs to this monotypic succulent herbaceous family, which is endemic to the Argentine Monte eco-region, in arid and semi-arid scrubland. Some have suggested a relationship with Chenopodiaceae and others a close relationship with Basellaceae and/or Portulacaceae. We performed detailed phylogenetic analyses using the nuclear (18S, ITS, and 26S) and plastid regions (atpB, trnK/matK, ndhF, rbcL, and rpl16) of previous and newly obtained DNA sequences in the suborder Portulacinae to clarify Halophytum’s relationships and to identify the DNA markers with the strongest phylogenetic signal. Phylogenetic analyses performed with the total evidence data matrix confi rmed a close relationship between Halophytum and Basellaceae and a close relationship of both with Didiereaceae. The DNA marker with the most parsimony informative sites was the plastid trnK/matK, followed by ndhF. When the proportion of variable to informative sites is considered, the nuclear ITS region retrieved the most informative sites. However, phylogenetic trees retrieved by total evidence analyses improve branch support if this nuclear region is not used.